NETIZENS OPINIONS ON LAW ENFORCEMENT AND SOCIAL RESPONSIBILITY - Hartanto, Hartanto; Santoso, Agus (Program Studi Hukum Fakultas Hukum Universitas Buana Perjuangan Karawang, 2024)
Netizens/netizens in Indonesia have a role in the disclosure of several legal cases. Therefore, this study aims to capture how the opinions and aspirations (Opinions) of netizens related to the positive law enforcement process in the criminal case of theft of cocoa beans charged to Grandma Minah (Case No. 247/Pid.B/2009/PN. PWT). The case of Grandma Minah is considered a case that disturbs the community's sense of justice. Netizens assessed that dragging Grandma Minah into the legal process just because of the theft of 3 cocoa grains was an irony and contrary to conscience. Netizens contrast the disparity between the firmness of law enforcement in the Grandma Minah case and the firmness of law enforcement in corruption cases or cases involving the rulers and the powerful. The spirit of Law 40/2007 on the Company directs the existence of corporate social responsibility (CSR) which can also be used as a benchmark to view this case. In this study, the opinions of netizens are classified as positive because they hope that the law can be more just, humane and conscientious. However, in the future, the potential for the opinions of netizens, which is sometimes also based on minimal data/facts, has the potential to distort the independence of judges.